(untitled) (Quinto Sol, 2023)
The order of books and libraries allows scholars to explore complex aspects of cultural and intellectual history, such as the organization of knowledge, the understanding of reality, and the different ways of classifying information. Taking into account these possibilities, this work analyzes the order of books in the libraries of the Jesuit-Guaraní missions (17th-18th centuries, Paraguay). The sources consulted are the inventories of goods belonging to the missions, produced as a consequence of the Jesuits’ expulsion from the Spanish Empire (1767-1768). The hypothesis is that the missionaries organized the libraries by topics according to a hierarchical criterion. The knowledge considered most significant from an epistemological point of view was located at the beginning of the inventories, but likely also in terms of space and accessibility. The remaining contents were situated subsequently in a progressive arrangement. At the same time, this work suggests that the organization was inspired by the Bibliotheca Scriptorum Societatis Iesu, i. e., a corporate bibliographical proposal developed within the Society of Jesus.